Exploring Our World - Martin, Jacqueline (Oxford University Press, 2010)
The Exploring Our World Activity Book provides: Additional reading, writing, and grammar practice for each chapter of the reader Consolidation activities A book review Answers to the activities can be found on the teacher's website